Quantitative revealing of reversed tension-compression yield asymmetry of an extruded Mg-Gd-Y-Zn-Zr alloy - Yuanqing Chi; Zihan Chen; Mingjie Shen; Mingyi Zheng; Weiqing Liu (Journal of Materials Research and Technology)
An extruded Mg-8.5Gd-2.5Y-0.5Zn-0.3Zr (wt%) alloy, characterized by a <101‾0> fiber texture with the [101‾0] axis aligned along the extrusion direction (ED) and a prismatic texture with basal planes oriented perpendicular to the ED, exhibits a reversed yield asymmetry (RYA). To quantitatively investigate this asymmetric behavior, in-situ synchrotron diffraction testing and polycrystal plasticity simulations were conducted. Under tensile loading, macroscopic yield is primarily driven by plastic deformation across most grains through basal slip, prismatic slip and tensile twinning, contributing 44%, 34% and 22% to the overall deformation, respectively. In contrast, under compressive loading, the initial yield involves a combination of plastic deformation in certain grains and elastic deformation in grains with prismatic textured. This “composite effect”, stemming from the elastic response of the prismatic textured grains, enhances the compressive yield strength. At a later stage, <c+a> slip is activated within the prismatic textured grains, contributing 16% to the overall deformation. The stronger strain hardening associated with <c+a> dislocations compared to other slip systems further enhances the compressive strength. Therefore, the RYA arises from variations in the active deformation mechanisms under different loading conditions, largely influenced by the presence of prismatic textured grains.